2002
DOI: 10.1046/j.1365-313x.2002.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar membrane localization of the Arabidopsis‘two‐pore’ K+ channel KCO1

Abstract: SummaryPotassium (K + ) channels play multiple roles in higher plants, and have been characterized electrophysiologically in various subcellular membranes. The K + channel AtKCO1 from Arabidopsis thaliana is the prototype of a new family of plant K + channels. In a previous study the protein has been functionally characterized after heterologous expression in Baculovirus-infected insect cells. In order to obtain further information on the physiological function of AtKCO1, the gene expression pattern and subcel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 54 publications
2
93
0
1
Order By: Relevance
“…While expression of the unmodified TT12 cDNA fully complemented the tt12 mutant phenotype (including returning Q3R and insoluble and soluble PAs to wild-type levels; Figure 2), the Pro35S-dual:GFP5:TT12:t35S construct restored flavonoid levels at ;75, 37, and 20% of the wild-type amount of Q3R and insoluble and soluble PAs, respectively (Figure 2), suggesting that a significant portion of GFP-cTT12 protein reached its proper destination within the cell and was functional. Transient expression by biolistic particle delivery of GFPcTT12 together with the established tonoplast marker TPK1 (Czempinski et al, 2002) fused to DsRed2 in onion bulb epidermis cells demonstrated that both proteins coreside on membranes (see Supplemental Figure 1A online). Importantly, fluorescence of both fusion proteins is visible on strands traversing the vacuole.…”
Section: Tt12 Is Localized To the Tonoplastmentioning
confidence: 99%
“…While expression of the unmodified TT12 cDNA fully complemented the tt12 mutant phenotype (including returning Q3R and insoluble and soluble PAs to wild-type levels; Figure 2), the Pro35S-dual:GFP5:TT12:t35S construct restored flavonoid levels at ;75, 37, and 20% of the wild-type amount of Q3R and insoluble and soluble PAs, respectively (Figure 2), suggesting that a significant portion of GFP-cTT12 protein reached its proper destination within the cell and was functional. Transient expression by biolistic particle delivery of GFPcTT12 together with the established tonoplast marker TPK1 (Czempinski et al, 2002) fused to DsRed2 in onion bulb epidermis cells demonstrated that both proteins coreside on membranes (see Supplemental Figure 1A online). Importantly, fluorescence of both fusion proteins is visible on strands traversing the vacuole.…”
Section: Tt12 Is Localized To the Tonoplastmentioning
confidence: 99%
“…VK currents may be mediated by members of the TPK/KCO K + channel family, encoded in Arabidopsis by six genes. KCO1/TPK1 was the first K + channel to be localized to the plant tonoplast [145] and, like VK currents of guard cells, when heterologously expressed in yeast KCO1 channels exhibit K + selectivity, activation by Ca 2+ , and voltage independence [146].…”
Section: Vacuolar Ion Transporters: Properties and Regulationmentioning
confidence: 99%
“…4). As a vacuolar control we used the C-terminal DsRed-tagged KCO1 channel from Arabidopsis (At5g55630), known to reside in the vacuolar membrane (Czempinski et al, 2002).…”
Section: Specification Of New Tonoplast Proteinsmentioning
confidence: 99%